A Study on the gonado Protective Role of Folinic Acid Against Cyclophosphamide Induced Cytotoxicity in Rat - Afsan, Md; Begum, Shahanaz; Ahmed, AH Hamid (Bangladesh Journal of Anatomy, 2013)
DOI: http://dx.doi.org/10.3329/bja.v9i2.15280 Bangladesh Journal of Anatomy 2011 Vol.9(2) pp.96-100